2018
DOI: 10.1123/jcsp.2017-0007
|View full text |Cite
|
Sign up to set email alerts
|

Injury and Disordered Eating Behaviors: What is the Connection for Female Professional Dancers?

Abstract: Dancers, like athletes, frequently endure injuries and disordered eating as a result of performance-specific demands. The purpose of this study was to explore the relationship between severe injuries and disordered eating from the perspectives of female professional dancers. In-depth, semi-structured interviews were conducted with 13 female professional dancers ages 18–38 (M = 23; SD = 6.2) whose dance participation was suspended for 4–36 weeks (M = 12.69; SD = 10.09) due to a dance-related injury. We adopted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(21 citation statements)
references
References 29 publications
6
15
0
Order By: Relevance
“…negative feelings of self‐worth associated with weight gain) and physical healing in high‐performance individuals. For example, work by Reel and colleagues (2018) with professional dancers revealed that injury‐induced modifications to dancers’ nutritional intake (e.g. reduction of calories, control of food intake) to avoid weight gain during periods of increased physical inactivity.…”
Section: Acute Injury Phasementioning
confidence: 99%
See 2 more Smart Citations
“…negative feelings of self‐worth associated with weight gain) and physical healing in high‐performance individuals. For example, work by Reel and colleagues (2018) with professional dancers revealed that injury‐induced modifications to dancers’ nutritional intake (e.g. reduction of calories, control of food intake) to avoid weight gain during periods of increased physical inactivity.…”
Section: Acute Injury Phasementioning
confidence: 99%
“…Some dancers also highlighted negative thoughts and feelings towards their bodies during injury‐periods, indicating concerns over weight‐gain, muscle loss, and diminished dance‐specific fitness. Sport psychologists and nutritionists can work collaboratively to identify players who may be at‐risk for maladaptive eating behaviours and/or body‐dissatisfaction; to mitigate and/or treat such issues when they arise; and to provide players with nutrition programmes that ensure sufficient energy for repair and maintenance of lean mass (Reel et al, 2018).…”
Section: Acute Injury Phasementioning
confidence: 99%
See 1 more Smart Citation
“…D ancers face inherent risks for injury due to the artistry and physicality of dancing, and injury prevalence and musculoskeletal pain have been reportedly high in dancers of varying levels (e.g., Hincapié et al, 2008;Jacobs et al, 2017;Kotler et al, 2017;Skvarla & Clement, 2019). Psychologically, dancers' experiences with injury may include various emotional responses, such as a loss of self-identity (e.g., Air, 2013;Reel et al, 2018), yet research on psychological responses to dance-related injuries remains limited. It is possible that dancers' psychological responses to injury are similar to other types of sport athletes.…”
mentioning
confidence: 99%
“…Researchers have used these three phases to identify trends in psychosocial responses to injury during each phase (Clement et al, 2015). Although researchers have studied the phases of rehabilitation in relation to different types of sport athletes, fewer studies have been conducted on dancers' injuries, and most do not follow a phased approach to rehabilitation (e.g., Macchi & Crossman, 1996;Reel et al, 2018). Due to the limited research on injured dancers, it is unknown whether dancers follow similar phases of rehabilitation as sport athletes.…”
mentioning
confidence: 99%